Preoperative risk assessment and prehabilitation strategies in patients undergoing an esophagectomy for cancer resections: a single center retrospective analysis and a review of the literature - González Santos, Silvia; Martí Gelonch, Laura; González Jorrín, Nuria; González Osinalde, Mireia; Rosell Romero, Núria (Frontiers in Anesthesiology, 2024)
Esophagectomy remains being a surgical procedure with a high morbidity and mortality rate. Therefore, prehabilitation, defined as the group of interventions performed on the patient in the preoperative period to improve their functional capacity and clinical condition, becomes highly important to ensure that the patient faces the stress that surgery entails under the best possible clinical situation. Hereby, we describe our prehabilitation protocol that has been implementedsince 2017 and we present the clinical results achieved so far. Preoperative risk assessment and various modalities of prehabilitation protocols are discussed to enhance the patient´s preoperative physiological condition and to reduce the impact of the neuroendocrine and inflammatory response induced by an esophagectomy.Finally, we describe the protocol we intend to implement to improve our clinical practice and reduce complications.Eliminado: better conditions